Benjy’s Howl: From Symptom to Sinthome in William Faulkner’s The Sound and the Fury - Maurice EBILEENI (E-REA)
This article employs Jacques Lacan’s concept of the sinthome to discuss the consequences of William Faulkner’s experimental employment of the stream-of-consciousness narrative mode in writing The Sound and the Fury. Faulkner effectively evacuates the authoritative narrator who may mediate, and re-envision the Compsons’ experiences from a privileged position. Instead, the composition of their experiences is held together by something else – a symptom. Psychoanalytically, the absence of a reliable narrator creates a discursive space devoid of authority, not unlike the psychotic’s reality. Composed of multiple voices in the “stream-of-consciousness” narrative mode, The Sound and the Fury’s “parallactic” narrative structure suggests a context of psychosis in which the deeply retarded Benjy Compson’s unintelligible howl functions as a symptom – or rather, I will argue, as a sinthome – a word-concept from the later Lacan which I employ here to refer to that which organizes the excess of textual jouissance in the absence of a unifying, authoritative narrator. Narration, therefore, in The Sound and the Fury does not move from the Symbolic to the Real to unveil the kernel of Benjy's cryptic enunciation as would have been expected in a neurotic context. Rather, it emerges through the invention of a sinthome.